The Triple Helix of innovation: a case study of the role and social relations of universities, industry and government - Noor Ashikin Said,; Zaharul Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The world economic is constantly changing and innovation is one of the keys to remain competitive. The Triple Helix model has been used as a tool to speed up and improve innovation spurt in many countries, especially a developing country such as Malaysia. The government has taken many steps to move Malaysia towards knowledge-based and innovation-based economy, and this Triple Helix model serves as a mechanism to boost the transition. This study attempts to investigate the challenges that arise in the dynamic collaboration of university, industries and government using the Triple Helix model within the context of the Malaysian’s development goals. This study uses semi-structured interviews to gather information and ten participants were selected from the three key spheres of the Triple Helix model: government (government personnel), universities (researchers and research management team), and industries (researchers, managers and executives). The semi-structured interviews were analyzed using a thematic analysis approach. The findings show that there are different facets of challenges faced by the triad collaboration including technological barriers, cultural differences, communication issues, and policy implementation hurdles. The most significant challenge identified was the organizational and structural discrepancies between industries and universities. Despite these challenges, the Triple Helix model remains a potent mechanism for driving innovation and fostering economic growth. Universities are adapting to this model, though issues related to commercialization and procedural inefficiencies persist.